2008
DOI: 10.1002/ptr.2561
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antiobesity effects of the protopanaxadiol‐ and protopanaxatriol‐type saponins of red ginseng

Abstract: A previous study demonstrated that ginseng crude saponins prevent obesity induced by a high-fat diet in rats. Ginseng crude saponins are known to contain a variety of bioactive saponins. The present study investigated and compared the antiobesity activity of protopanaxadiol (PD) and protopanaxatriol (PT) type saponins, major active compounds isolated from crude saponins. Male 4-week-old Sprague-Dawley rats were fed with normal diet (N) or high-fat diet (HF). After 5 weeks, the HF diet group was subdivided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 42 publications
1
40
0
1
Order By: Relevance
“…Several studies suggested that RG intake reduced body weight and fat content [18,19,20]. RG intake down-regulated genes associated with lipid metabolism, which are up-regulated by a high-fat diet [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that RG intake reduced body weight and fat content [18,19,20]. RG intake down-regulated genes associated with lipid metabolism, which are up-regulated by a high-fat diet [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that the R1 exerted a protective effect against hepatic injury prompted by H 2 O 2 treatment in previous studies ). Also, previous studies reported that PD types of ginsenosides were effective not only in improving conditions of obesity, fatty liver, and hypertriglyceridemia in rodent models fed with a high-fat diet (Liu et al 2010;Kim et al 2009) but also in regulating inflammatory responses by inducing heme oxygenase (HO)-1, inhibiting inducible nitric oxide synthase (iNOS), and suppressing the tumor necrosis factor (TNF)-a expression in vitro (Lee et al 2005;Cho et al 2006). Moreover, ginsenoside PTs inhibit energy gain and normalize hypothalamic neuropeptides associated with the control of obesity in rats ) and have a cytoprotective effect through their action against oxidative stress by blocking an increase in LPS-induced iNOS and COX-2 expressions via control of NFjB, which may be responsible for the chemoprevention of inflammatory diseases (Kwok et al 2010;).…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside in ginseng, namely triterpenoidal dammarane saponin, which is uniquely present in the Panax species, is divided into protopanaxadiols (PDs) and protopanaxatriols (PTs). The PDs, including ginsenoside Rb1, Rb2, Rc, and Rd, have an anti-obesity effect (Liu et al 2010;Kim et al 2009) and exhibit anti-inflammatory activity (Lee et al 2005), whereas the PTs, such as ginsenoside Re, Rf, and Rg1, have efficacy on the prevention of oxidative stress (Kwok et al 2010) and the modulation of inflammatory processes ). These reports show that each ginsenoside has different biological effects, but their synergetic properties in hyperlipidemia have not been examined so far.…”
mentioning
confidence: 99%
“…Chronic administration of an extract of ginseng root significantly reduced body weight, fat mass, and serum lipids in diet-induced obese rats (7,8), and extracted ginseng has also been reported to ameliorate hyperglycemia in animals and humans (912). In one report, both diabetic and nondiabetic subjects taking an extract of ginseng had stabilized postprandial glycemia, suggesting that ginseng may also benefit healthy individuals (13).…”
mentioning
confidence: 99%